Díaz, Onésimo, Florentino Pérez Embid. Una biografia (1918-1974), Madrid, Ediciones Rialp, 2023, 651p. ISBN: 978-84-3216-499-6; eISBN: 978-84-3216-500-9. 29€ - Álvaro Ferrary (Memoria y Civilización, 2023)
Book Review